Interactions of age and leg muscle fatigue on unobstructed walking and obstacle crossing - Barbieri, Fabio Augusto [UNESP]; Rocha dos Santos, Paulo Cezar [UNESP]; Simieli, Lucas [UNESP]; Orcioli-Silva, Diego [UNESP]; van Dieen, Jaap H.; Bucken Gobbi, Lilian Teresa [UNESP] (Elsevier B.V., 2014)
Older adults commonly report muscle fatigue, which may be associated with reduced walking ability. Elderly may have insufficient awareness of the balance threat caused by muscle fatigue. The aim of this study was to analyze the interaction effects of aging and leg muscle fatigue on gait parameters in walking and obstacle crossing. One hundred and twenty men, who were divided in six groups according to their age (20-29 years, 30-39 years, 40-49 years, 50-59 years, 60-69 years, above 70 years), participated in this study. Participants performed three trials of unobstructed level ground walking and obstacle crossing during walking before and after quadriceps muscle fatigue. To induce fatigue, participants performed a repeated sit-to-stand task from a chair with arms across the chest to a pre-determined cadence (30 cycles/min) using a metronome. Spatial-temporal gait parameters (stride length, duration, and speed, step width, and trailing and leading heel-clearance) were analyzed, and compared by two-way ANOVA (group and fatigue). The results confirmed our hypothesis, showing age-related effects of leg muscles fatigue in both gait conditions. From 40 years old, participants modulated spatial-temporal and vertical impulses in both tasks more in response to fatigue than younger participants, apparently to improve balance and safety. Leg muscle fatigue caused age-dependent changes in both unobstructed level ground walking and obstacle crossing during walking, which appeared to reflect an attempt to maintain balance and safety, probably to counteract adverse fatigue effects. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Walking; Muscle fatigue; Aging; Obstacle avoidance; Human movement